Molecular biophysics for the life sciences - Narhi, Linda O.; Rayment, Ivan; Allewell, Norma (Biophysics for the Life Sciences, 2013)
This volume of the series Biophysics for the Life Sciences focuses on the conceptual framework and major research tools of contemporary molecular biophysics.  It is designed to enable non-specialists-both students and professionals in other fields-to understand how these approaches can be used across the biosciences and in medicine, agriculture, biotechnology, pharmaceutical development and other fields.  The scope of this volume is appropriate for advanced undergraduate and graduate courses in biophysics and biophysical chemistry.   The book begins with an overview of the development of molecular biophysics and a brief survey of  structural, physical, and chemical principles.  Subsequent chapters written by experts present, with examples, the major experimental methods: optical spectroscopy, X-ray and neutron diffraction and scattering, nuclear magnetic resonance, electron paramagnetic resonance, mass spectrometry, and single molecule methods.  The relationship between the biophysical properties of biological macromolecules and their roles as molecular machines is emphasized throughout and illustrated with three examples-DNA helicases, rotary motor ATPases, and myosin.  The concluding chapter discusses future prospects in X-ray and neutron scattering, mass spectrometry, and pharmaceutical development.    Dr. Norma M. Allewell is Professor of Cell Biology and Molecular Genetics and Affiliate Professor of Chemistry and Biochemistry at the University of Maryland, where she served as Dean of the College of Chemical and Life Sciences for a decade. Her research focuses on protein structure, function and dynamics, and metabolic regulatory mechanisms and diseases.   Dr. Linda Narhi is a Scientific Executive Director in the Product Attribute Science Group at Amgen, where her responsibilities include solution stability assessment of all protein-based therapeutic candidates, and developing and implementing predictive assays for protein stability to process, storage, and delivery conditions.   Dr. Ivan Rayment is Professor of Biochemistry at the University of Wisconsin-Madison, where he holds the Michael G. Rossmann Professorship in Biochemistry. He has a wide range of interests in structural biology and has made seminal contributions to our understanding of the structural basis of motility, enzyme evolution, cobalamin biosynthesis, and transposition.